Diagnostic accuracy of procalcitonin, interleukin-6 and interleukin-8 for predicting Gram-negative bacteremia in febrile neutropenia patients with acute lymphoblastic leukemia - Urbonas, Vincas; Eidukaitė, Audronė (Acta medica Lituanica, 2015)
Background. Currently available biomarkers are not specific and sensitive enough for early detection of bacterial infection in patients with cancer who have febrile neutropenia. The objective of this study was to assess diagnostic accuracy of interleukin-6 (IL-6), interleukin-8 (IL-8) and procalcitonin (PCT) in the identification of Gram-negative bacteremia at the beginning of a febrile episode in pediatric oncology patients with acute lymphoblastic leukemia (ALL). Methods. A total of 40 episodes of febrile neutropenia in 27 childhood cancer patients were enrolled in this study. Serum samples were collected at presentation after confirmation of febrile neutropenia and analyzed according to the recommendations of manufacturers. Patients were classified into Gram-negative bacteremia (GNB) and fever of unknown origin (FUO) groups. Results. The median concentration of IL-6, IL-8 and PCT were higher in the GNB group compared to the FUO group (65.4  vs.  409.0  pg/ml, P  =  0.0025; 166.0  vs.  883.0  pg/ml, P  =  0.0002; 0.27  vs.  0.44  ng/ml, P = 0.0169, respectively). The areas under the curves (AUCs) for both IL-6 and IL-8 were 0.94 and 0.93, respectively, indicating that these cytokines discriminated patients with Gram-negative bacteremia with excellent accuracy, whereas PCT had lower diagnostic accuracy (AUC = 0.76). Conclusions. IL-6 and IL-8 evaluation might be used as an additional diagnostic tool for the prediction of Gram-negative bacteremia in pediatric patients with ALL during febrile neutropenia episodes.
Keywords: procalcitonin; interleukin-6; interleukin-8; febrile neutropenia; leukemia; bacteremia